Bioprocessing of Jackfruit Seeds (Artocarpus heterophyllus Lam.) for Protein Enrichment in Semi-Solid State: Potential for Animal Feed Production - Ana Paula Moisés de Sousa; Ana Regina Nascimento Campos; Josivanda Palmeira Gomes; Renato Alexandre Costa de Santana; Alexandre Jose de Melo Queiroz; Rossana Maria Feitosa de Figueirêdo; Mailson Gonçalves Gregório; Newton Carlos Santos; Wilton Pereira da Silva; Michael Marcos de Aquino Gomes; Morgana Aragão Araújo; Francislaine Suelia dos Santos; et al. (Fermentation)
Jackfruit residues represent 70% of the total by-products generated from the processing of the fruit. The seeds, which are composed of proteins, fibers, and starch, are widely used in human nutrition; however, its potential in animal nutrition should be further investigated. Thus, the objective was to study the protein enrichment of jackfruit seeds by semi-solid fermentation using Saccharomyces cerevisiae and applying an experimental design to verify the effects of yeast concentration (1, 3, and 5%) and process temperature (30, 35, and 40 °C) on the protein increase. Physical and chemical analysis of the substrate was performed at intervals of 0, 24, 48, 72, and 96 h. A decrease in water content and water activity was observed during the fermentation time. The total soluble solid content also declined due to the consumption of carbohydrates by yeast. After 96 h of the process, the crude protein content of the fermented substrate increased approximately 2.5 times, corresponding to a protein increase of 357%, with the use of 5% of yeast at 40 °C. Through semi-solid fermentation, the protein content and the concentration of mineral nutrients in the jackfruit seeds increased, making it an alternative product for animal feed with high added value.